Economic Statecraft and Strategic Hedging: A Neoclassical Realist Analysis of Qatar’s Housing Investment in Indonesia - Ilham Dary Athallah; Hayara Khairia; Tsabita Husna; Ronna Rihadatul Aisy; Zaskia Nurwati Azzahra (MD Research Center, 2026)
This study examines Qatar’s investment in Indonesia’s one million homes program (2024–2026) through the lens of classical realism to reveal the strategic calculations underlying development cooperation between Gulf states and Southeast Asia. Against the backdrop of Indonesia’s acute housing deficit and Qatar’s surplus capital, this research addresses a gap in understanding how power dynamics and national interest shape South-South development finance. Employing a qualitative explanatory single-case design with process tracing and document analysis, this study systematically examines official documents, media reports, and think-tank analyses from December 2024 to March 2026. The findings demonstrate that Qatar’s investment serves as economic statecraft to project geopolitical influence and compensate for military limitations, while Indonesia leverages foreign capital as a self-help mechanism to address domestic stability threats and preserve strategic autonomy through partnership diversification. The study concludes that even apparently altruistic development partnerships are fundamentally shaped by power calculations and interest-balancing. This research contributes a realist account of Gulf-Asia relations and introduces the concept of “balance-of-partnership diversification” as a framework for understanding how middle powers maintain autonomy in an anarchic international system. The findings offer policy guidance for managing the strategic dimensions of development finance, emphasizing the importance of diversified partnerships and delivery credibility.